Light or Ethylene Treatments Induce Transverse Cell Enlargement in Etiolated Maize Mesocotyls - Camp, Pamela J. (1981)
Dark-grown maize seedlings (hybrid WF-9 × 38-11) exposed for 1 or more hours to white light and then returned to darkness developed mesocotyls with enlarged apical diameters. This swelling response was an all-or-none response, and the fraction of the seedling population that showed the response depended on seedling age at irradiation. Irradiation of the coleoptile alone was nearly as effective in causing this response as was irradiation of the nodal region of the epicotyl, but irradiation of the mesocotyl base was ineffective. Removal of the coleoptile prior to irradiation did not prevent the formation of the light-induced swelling. Exogenously applied C(2)H(4) (10 microliters per liter) for 24 hours in dark also induced swelling of the mesocotyl. The swelling induced in the intact seedlings was localized in the apical mesocotyl tissues with either light or C(2)H(4) treatment, and maximal response to both treatments occurred with 3- to 4-day-old seedlings. Swelling of the mesocotyl was the result of transverse cell enlargement, not increase of cell numbers. The evidence suggests that light and C(2)H(4) induce mesocotyl swelling in intact maize shoots by a common mechanism.